DEVELOPMENT OF INFRASTRUCTURE AND SUPPORTING FACILITIES FOR THE MINAPOLITAN AREA (Case Study: Kecamatan Pinogaluman Kabupaten Bolaang Mongondow Utara Provinsi Sulawesi Utara) - Alamri, Siti Aviva Mustika; Supardjo, Surijadi; Sembel, Amanda (SPASIAL, 2021)
Indonesia has a coastal area that will be known for its enormous resource potential, biodiversity, the potential for aquaculture and marine tourism potential which can be found in almost every corner of the area in its aquatic ecosystem. The basic concept of developing the minapolitan area is an effort to create balanced development between regions, especially by increasing the urban-rural linkage, namely the development of rural areas that are integrated into the urban system functionally and spatially. The fisheries sector has a comparative advantage compared to other sectors, in the form of the availability of very large natural resources and is able to produce highly competitive products and services. Most fishermen in Pinogaluman District are still far from the level of welfare, there are still obstacles experienced in the development of the Minapolitan area, one of which is the problem of the availability of infrastructure and facilities to support the development of the Minapolitan area in Pinogaluman District which is not sufficient, so it cannot support the Minapolitan area. The method used is a qualitative descriptive analysis method which is used to describe the existing condition of the infrastructure and supporting facilities of the Minapolitan area, the GAP analysis is used to provide a description related to the condition of the infrastructure and facilities of the Minapolitan area, and the analysis of development directions is used to determine the development method by analyzing external factors in the form of opportunities and threats and internal factors in the form of strengths and weaknesses. The results of the matrix analysis of the development of infrastructure and supporting facilities for the minapolitan area in Pinogaluman District are in quadrant I by looking at the strengths and opportunities in resources, providing a special strategy for the form of development of the minapolitan area. In the SO strategy, with full support from government efforts, it is hoped that there will be appropriate spatial planning. In addition, more resources are needed to repair damaged infrastructure and facilities. There are also publications regarding the minapolitan area so that this area can be paid more attention by the government. The last is to provide easy accessibility for people who are involved in Minapolitan activities, so that production activities will increase and will not be recorded. Keywords : Minapolitan, Infrastructure and Facilities, Development